A formação integrada omnilateral: fundamentos e práticas no Instituto Federal de Goiás a partir do Proeja - Barbosa, Sebastião Cláudio (2017)
This work binds the research line "Fundamentals of Educational Processes" (V-Line) of the graduate program of the Faculty of Education of the Federal University of Goiás (PPGE/FE/UFG). It is a bibliographical and a theoretical study, but that has as its starting point in the author's experience as a teacher of IFG (Instituto Federal de Goiás, Campus Goiânia) since 2008 and, fundamentally, the analysis of the reports of realized experiences and points of view on the integrated training within this Institution in the technical integrated courses of medium level of Proeja – National Program of the Professional Education with the Basic Education in the modality of the Youth and Adult Education – particularly in the Technical Integrated Course in Cooking. It was took as a starting point the confirmation of the existence of such an object that is the Omnilateral Integrated Formation and also Proeja, here understood as the "gateway" to think and realize that pedagogical perspective in Federal Institutes. It was sought from the demands for conceptualization of the reports and also from the already mentioned experience to conceptualize the fundamentals of Integrated Training Omnilateral (ethics, interdisciplinary, integrated curriculum, developmental education) according to the principles of praxis. That is, it was sought a form of categorization in which the larger sense is the determination of the existence in its historical mode. For this purpose it was used the contribution of various authors: Karl Marx, Antonio Gramsci, George Lukács, Karel Kosik, Adolfo Sánchez Vázquez, Vasili Davydov, Gaudencio Frigotto, Maria Ciavatta, Acacia Kuenzer, Lucília Machado, Miguel Arroyo, Moacir Gadotti, Marise Ramos, Mad'Ana Castro, Jacqueline Vitorette among others. For the realization of the documentary aspect, it was used the documents related to the creation of the Federal Institutes and Proeja, the written transcriptions of lectures and exchange of experiences occurred in the "Dialogues EJA", performed by Rodrigo Freitas Amorim, available in Adult and Youth Education Forum Portal (Portal do Fórum EJA). The conclusions show that the "Integrated Training Omnilateral as pedagogical praxis" exists as verifiable phenomenon in Federal Institutes. However, its checking count with an apprehension that shows the "visible" committed to the analysis of its "invisible" historicity. With these essential characteristics, such an object was only possible to be verified against hegemony and revealed as abstract-concrete like concrete thought.